"A Wonderful Song of Wood": Heritage Architecture and the Search for Historical Authenticity in North Russia. Issue 1 (2nd January 2017) - Golubev, Alexey
Abstract : This article examines architectural preservation in North Russia after World War II as a movement that treated local vernacular architecture as a key to understanding the authentic national history of Russia. It argues that Soviet architectural preservationists were driven by romantic nationalist ideas that sought to establish northern Russian vernacular architecture as an aesthetic system that fully realized the expressive potential of wood as a construction material. Moreover, Soviet preservationists linked this system to a society free of the social conflicts that allegedly existed in North Russia, thanks to its geographic and political marginality until the tsarist oppression of the nineteenth century. While widely employing the conceptual apparatus of early Soviet-Marxist architects such as Moisei Ginzburg and Aleksei Gan, Soviet architectural preservationists petrified the transformative social agenda of early Soviet architectural theory.